Of Race, Prison, and Perception: Seeking to Account for Racially Divergent Views on the Relative Severity of Sanctions - Applegate, Brandon K. (American journal of criminal justice, 2014)
Several studies have found that offenders do not always perceive prison to be a harsher sanction than community-based punishments. Moreover, the literature shows that white offenders tend to estimate prison to be relatively more severe than do black offenders. The present study develops and tests eight possible explanations for the observed racial gap in perceptions. Relying on survey data from inmates in a large urban jail to establish sentencing preferences for black and white inmates, multivariate analyses show that the racial gap was attenuated but not eliminated by the explanations. This persistent racial difference in opinions of sanction severity is consistent with differential perceptions of criminal justice system fairness and merits additional research. The race gap has implications for theories on the effects of incarceration as well as sentencing practice.